TANTANGAN SELEKSI GURU DI ERA DIGITAL: ANTARA PROFESIONALISME DAN SPIRITUALITAS DALAM PENDIDIKAN ISLAM - Kholida, Anif; Sukarman, Sukarman; Haji, Nur; Wafda, Mahfud (STKIP Pesisir Selatan, 2025)
Digital transformation in the world of education demands fundamental changes in the teacher selection process, including in Islamic education environments. Teachers are not only required to have professional competence and mastery of technology, but also spiritual integrity that reflects Islamic values. This study aims to examine the challenges of teacher selection in the digital era, and to offer an integrative selection approach between professionalism and spirituality. Using a literature study method with a qualitative descriptive approach, data was obtained from national and international scientific literature. The results of the study indicate an imbalance in digital literacy, the dominance of technical professionalism aspects, and weak instruments for measuring spirituality in the teacher selection process. Therefore, a multidimensional and collaborative selection model is needed, including integration between madrasahs and Islamic boarding schools, in order to produce teachers who are balanced between technological skills and moral-spiritual strength in educating the Islamic generation. This study aims to formulate a teacher selection strategy that is not only oriented towards technological and pedagogical skills, but also considers spiritual qualities and personality integrity that are in line with the mission of Islamic education. In addition, this paper also examines how an integrative approach between professionalism and spirituality can be implemented in real terms in digital-based teacher selection.